Description of two Staurois tadpoles from Borneo, Staurois parvus and Staurois tuberilinguis (Anura: Ranidae) - Grosjean, Stéphane; Preininger, Doris (Zootaxa, 2020)
The external morphology of two molecularly identified tadpoles of the genus Staurois, S. parvus and S. tuberilinguis is described. These tadpoles display a typical fossorial morphology characterized by a strongly depressed body, small subcutaneous eyes, a vermiform appearance with a long tail and reduced fins, a nearly pigmentless skin, a KRF of 1:1+1 on the upper labium and numerous keratodont rows on the lower one. The two species can be distinguished by several morphological differences, the most conspicuous are the eye condition (not bulging and covered by skin in S. tuberilinguis) and the presence of numerous white isolated acini on the body and tail in S. parvus. These differences support the specific status of S. parvus relatively to S. tuberilinguis despite low genetic divergence between these two taxa. The morphology of these tadpoles, as well as the buccopharyngeal anatomy of S. parvus, are compared to those of the tadpoles in the family Centrolenidae and the definition of the fossorial ecomorphological guild is updated.